Pengaruh Organizational Justice, Ethical Leadership, dan Kompensasi terhadap Employee Engagement: (Studi pada karyawan PT Kredivo Finance Indonesia di Slipi Jakarta Barat) - Salma Safitri; Yuni Kasmawati (Journal of Management and Creative Business, 2024)
This study aims to determine the effect of Organizational Justice, Ethical Leadership, and Compensation on Employee Engagement at PT Kredivo Finance Indonesia in Slipi, West Jakarta. The sample in this study were 50 employees of PT Kredivo Finance Indonesia in the collection earlyownership section. The data was collected through a questionnaire with a Likert scale which was processed using Microsoft Excel 2019 Software and SPSS Software version 26. The sampling technique used in this study is saturated sampling technique. The research method used is multiple linear regression. The results of this study indicate that Organizational Justice has a positive and significant effect on Employee Engagement, Ethical Leadership has a positive and significant effect on Employee Engagement while the compensation variable has no significant effect on Employee Engagement.